Time trends of the prevalence of asthma, rhinitis and eczema in Thai children-ISAAC (International Study of Asthma and Allergies in Childhood) Phase Three - Trakultivakorn M. (2014)
Using the same questionnaire as in ISAAC Phase One study conducted in 1995, the ISAAC Phase Three was carried out in Bangkok and Chiang Mai, Thailand, in 2001, among children aged 6-7 and 13-14 years. There was an increase in the prevalence of the three diseases in the younger age group, i.e., current asthma, rhinitis, rhinoconjunctivitis, and flexural eczema. In the older age group, the prevalence of rhinitis and rhinoconjunctivitis increased. There was no change of prevalence of asthma in Bangkok, but prevalence decreased in Chiang Mai. Prevalence of eczema in older children increased in Bangkok, but remained the same in Chiang Mai. Copyright © 2007 Informa Healthcare USA, Inc.